2010
DOI: 10.1007/s10237-010-0270-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling for flow-activated chloride-selective membrane current in vascular endothelial cells

Abstract: In this paper, a dynamic model is proposed to quantify the relationship between fluid flow and Cl(-)-selective membrane current in vascular endothelial cells (VECs). It is assumed that the external shear stress would first induce channel deformation in VECs. This deformation could activate the Cl(-) channels on the membrane, thus allowing Cl(-) transport across the membrane. A modified Hodgkin-Huxley model is embedded into our dynamic system to describe the electrophysiological properties of the membrane, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…In recent years, the interactions between cells and extracellular microenvironments have received more attention in the field of cell biology [4][5][6][7][8]. Researches show that cells in response to dynamic signals exhibit different characteristics from those to static ones [9][10][11][12][13][14]. However, while most of the previous investigations focused on the cellular behaviors in response to static biomechanical and/or biochemical signals [9][10][11], few studied the effect of dynamic signals [12][13][14].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years, the interactions between cells and extracellular microenvironments have received more attention in the field of cell biology [4][5][6][7][8]. Researches show that cells in response to dynamic signals exhibit different characteristics from those to static ones [9][10][11][12][13][14]. However, while most of the previous investigations focused on the cellular behaviors in response to static biomechanical and/or biochemical signals [9][10][11], few studied the effect of dynamic signals [12][13][14].…”
Section: Introductionmentioning
confidence: 94%
“…Researches show that cells in response to dynamic signals exhibit different characteristics from those to static ones [9][10][11][12][13][14]. However, while most of the previous investigations focused on the cellular behaviors in response to static biomechanical and/or biochemical signals [9][10][11], few studied the effect of dynamic signals [12][13][14]. Thus, a controlled quantitative loading of dynamic biomechanical and biochemical signals on cells cultured in vitro is needed to provide more insights into the biological processes and behaviors of the cells.…”
Section: Introductionmentioning
confidence: 95%
“…Various in vitro loading techniques, such as cell swelling, substrate stretch loading and fluid shear stress (FSS), are used in the study of osteocyte response to mechanical stimulation. However, the majority of studies do not recapitulate osteoblast anabolism under mechanical stimulation, including the activation of intracellular chloride ions, chloride channel genes and channel proteins (3)(4)(5)(6)(7). In fact, studies have shown that numerous ion channels [such as Ca 2+ channels (8) and K + channels (9)] have a role in osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies focusing on the effects of oscillatory flow on cell cultures are rather rare. Qin et al (39) developed a mathematical model to investigate the interaction of the pulsatile and oscillatory flows with endothelial cells, especially the impacts of various flow regimes on the chloride transmembrane transport and the corresponding electric current. They showed that the endothelial cell can distinguish between the flow types by different electric current responses.…”
Section: Introductionmentioning
confidence: 99%